Reduced antioxiadant high-density lipoprotein function in patients with acute coronary syndrome. (3rd October 2022) - Pagonas, N; Weiland, L; Jaensch, M; Dammernmann, W; Christ, M; Ritter, O; Westhoff, T; Kelesidis, T; Sasko, B
Abstract: Background: High-density lipoprotein (HDL) function rather than concentration plays an important role in the pathogenesis of cardiovascular diseases associated with oxidative stress and inflammation such as coronary artery disease (CAD). In the last years, inflammation has been identified to have a pivotal role in the pathogenesis of acute coronary syndrome (ACS). Purpose: The aim of the present study is to determine whether reduced antioxidant function of HDL is associated with ACS. Methods: 197 patients with ACS were prospectively recruited and blood samples were taken in the first 48h after enrollment. Patients with chronic coronary syndrome CCS (n=727) and with invasively excluded CAD (no CAD, n=498) from another cohort from our group served as control patients. A validated cell-free biochemical assay was used to determine reduced HDL antioxidant function as assessed by increased HDL-lipid peroxide content (HDLox) normalized by HDL-C levels and the mean value of a pooled serum control from healthy participants (nHDLox; no units). Results: Patients with ACS had significantly increased HDLox blood levels compared to patients with CCS and to patients without CAD (p<0.001, Figure 1A). Prior intake of statins did not influenc the differences of HDLox among the groups (Figure 1B). In the regression analysis increased HDLox was a strong risk factor for the presence of ACS compared to CCS (odds ratio 4.09 (2.98–5.62), p<0.001, Figure 2). Conclusions: HDL peroxidation is associated with the presence of ACS independent of the presence of other traditional risk factors. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): BIOX